Determining the optimal time for liberation from renal replacement therapy in critically ill patients: protocol for a systematic review and meta-analysis (DOnE RRT). Issue 11 (25th November 2018) - Al Saadon, Abdalrhman; Katulka, Riley; Sebastianski, Meghan; Featherstone, Robin; Vandermeer, Ben; Gibney, R T Noel; Rewa, Oleksa G; Bagshaw, Sean M
Abstract : Introduction: Renal replacement therapy (RRT) is a complex and expensive form of life-sustaining therapy, reserved for our most acutely ill patients. While a number of randomised trials have evaluated the optimal timing to start RRT among critically ill patients in the intensive care unit (ICU), there has been a paucity of trials providing guidance on when and under what circumstances to ideally liberate a patient from RRT. We are conducting a systematic review and meta-analysis to identify clinical and biochemical markers that predict kidney recovery and successful liberation from acute RRT among critically ill patients with acute kidney injury. Methods and analysis: Our comprehensive search strategy was developed in consultation with a research librarian and independently peer-reviewed by a second librarian. We will search electronic databases: Ovid Medline, Ovid Embase and Wiley Cochrane Library. Selected grey literature sources will also be searched. Our search strategies will focus on concepts related to RRT (ie, intermittent haemodialysis, slow low-efficiency dialysis, continuous renal replacement therapy), intensive care (ie, involving any ICU setting) and discontinuation of therapy (ie, either clinical, physiological and biochemical parameters of weaning acute RRT) from 1990 to October 10, 2017. Citation screening, selection, quality assessment and data abstraction will be performed in duplicate. Studies will, where possible, be pooled in statistical meta-analysis. When deemed sufficiently clinically homogenous, and we have four or more studies reporting, sensitivities and specificities will be pooled simultaneously using a hierarchical summary receiver operator characteristic curve and bivariate analysis. Ethics and dissemination: Our systematic review will synthesise the literature on clinical and biochemical markers that predict liberation from RRT. Research ethics approval is not required. Trial registration number: CRD42018074615.